IPTEKS PENCATATAN PENDAPATAN ASLI DAERAH DI BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KOTA MANADO - Palenteng, Meylan Febiola; Datu, Christian (Universitas Sam Ratulangi, 2018)
Regional original income is regional income originating from the results of regional taxes, regional restitution, profits from regionally-owned enterprises, and other legitimate local revenues in exploring funding in the implementation of autonomy as a manifestation of the principle of decentralization. The purpose of this study is to analyze the comparison of the realization of local revenue in the Tax Management and Retribution Agency of the City of Manado during 2016-2017. The method used in this study is descriptive method. It's good that the leadership of the Regional Tax and Retribution Management Board of the City of Manado pays more attention to regional revenue so that there is no significant increase or decrease every year.Keywords : analysis of local revenue, recording, realization